The Effect of Using Learning Management Systems and On-the-Job Training on Improving Teachers' Professional Competence in In-Depth Learning in Bulukumba Regency - Rahmaniar; Hartini; Muhammad Fahreza W (EDUJAVARE: International Journal of Educational Research, 2026)
This study aims to determine the effect of the use of Learning Management System (LMS) and On The Job Training (OJT) on the professional competence of teachers in Bulukumba Regency, both partially and simultaneously. This study uses a quantitative approach with a survey method. Research data were obtained through distributing questionnaires to 18 respondents who are teachers in Bulukumba Regency. The data analysis technique used is multiple linear regression analysis which includes partial tests (t-test), simultaneous tests (F-test), and coefficient of determination with the help of a statistical data processing program. The results of the study indicate that partially the use of LMS has a significant effect on the professional competence of teachers, while the On The Job Training (OJT) variable also has a significant effect on the professional competence of teachers. Simultaneously, the use of LMS and the implementation of OJT have a significant effect on the professional competence of teachers. The Adjusted R Square value of 0.365 indicates that 36.5% of the variation in the professional competence of teachers can be explained by these two variables, while the rest is influenced by other factors outside the research model. Thus, the use of Learning Management System (LMS) and the implementation of On The Job Training (OJT) have a positive and significant effect on improving the professional competence of teachers in Bulukumba Regency.